Avaliação da profundidade de sulco gengival mésio-vestibular dos dentes 11 e 21 em pacientes submetidos à expansão de maxila cirurgicamente assistida; avaliação clínica da largura da base alar de pacientes submetidos à expansão cirurgicamente assistida de maxila - Assis, Diogo Souza Ferreira Rubim de (2010)
Surgically assisted maxillary expansion (SAME) has been used for treating transversal deficiency of the maxilla and it could result in alterations of skeletal, dental and teeth s support structures. Therefore, the aim of this study was to evaluate the modifications occurred in the mesio-buccal gingival sulcus depth of the upper right and left central incisors during a 3-year post-operative period. The mesio-buccal gingival sulcus depth of the upper right and left central incisors of patients with transversal deficiency of maxilla submitted to SAME was measured by using a periodontal probe, both in the pre-operative period and in the 2-, 6-, 24-, and 36- month post-operative period. The results were submitted to statistical analysis by using ANOVA and Tukey s test with level of significance of 5%. The mesial gingival sulcus depths of the upper right and left central incisors, although numerically different, were statistically significant (P<0.05) in the comparison between the preoperative and both the 2- and 6-month post-operative periods, between the 2- and 24-month post-operative periods, and between the 2- and 36-month periods. The gingival sulcus depths increased during the initial post-operative periods. Based on the data analysed by this study, the SAME procedure provoked changes in gingival sulcus depth of the upper right and left central incisors. Such changes could be shown by the increase of the gingival sulcus depth.